A single vectored thermal pulsation treatment for meibomian gland dysfunction increases mean comfortable contact lens wearing time by approximately 4 hours per day - Blackie, Caroline A (Clin Ophthalmol, 2018)
PURPOSE: To evaluate the effect of a single vectored thermal pulsation (VTP) treatment in contact lens wearers with meibomian gland dysfunction (MGD) and dry eye symptoms. METHODS: The prospective, nonsignificant risk, open-label, randomized, multi-center clinical trial included 55 soft contact lens (SCL) wearers with MGD and evaporative dry eye. Subjects were randomized to the single VTP treatment group or an untreated control. The controls received a crossover VTP treatment at 3 months (crossover treatment group). Primary effectiveness measures were meibomian gland secretion (MGS) score and Standard Patient Evaluation of Eye Dryness (SPEED) that were evaluated at baseline, at 1 and 3 months post-VTP treatment, and at 1 month post-VTP treatment in the crossover treatment group. Exploratory variables included fluorescein tear break-up time (TBUT), lid wiper epitheliopathy (LWE), lid parallel conjunctival folds (LIPCOF), ocular surface staining, frequency of over-the-counter (OTC) drop use, and hours of comfortable contact lens wear. RESULTS: At 3 months, the treatment group showed significantly greater mean change from baseline in MGS (12.4±9.1 vs 1.4±6.4, p<0.0001), SPEED (−8.4±4.7 vs −0.7±4.4, p<0.0001) and significantly greater improvement in exploratory variables (TBUT, LWE, and frequency of OTC drop use) relative to the controls. Mean comfortable contact lens wearing time increased by 4.0±3.9 hours at 1 month. This was sustained for 3 months with no change in the control group. The crossover treatment group demonstrated similar results to the treatment group at 1 month post-VTP. CONCLUSION: In SCL wearers with MGD, a single VTP treatment significantly improved mean meibomian gland function and significantly reduced dry eye signs and symptoms compared to an untreated control. The treatment increased mean comfortable lens wearing time by 4 hours (approximately doubling the pretreatment findings). This was sustained for up to 3 months post-treatment on average.